Integrated watershed management: connecting people to their land and water - Gregersen, H. M.; Brooks, K. N.; Brooks, K. N.; Ffolliott, P. F.; Ffolliott, P. F.; Gregersen, H. M. (Wallingford :CAB International, 2007)
This book provides background information and presents factors to be considered and procedures that facilitate organizing and guiding land and water use in concert with one another; it further serves as a reference for planning, monitoring and implementing development efforts and natural resource management through the lens of integrated watershed management (IWM). The eight chapters of this book are under the following headings: (1) Challenges and opportunities; (2) Land use, watershed management and cumulative effects; (3) Institutional context; (4) Planning and policy making; (5) Hydrologic processes and technical aspects; (6) Monitoring and evaluation to improve performance; (7) Research, training, information and technology transfer; and (8) Adaptive, Integrated Management of watersheds: Concluding thoughts.
Keywords: CC100 - Education and Training; CC200 - Extension and Advisory Work; EE120 - Policy and Planning; PP200 - Water Resources; PP300 - Land Resources